Clamping of RNA with PNA enables targeting of microRNA. Issue 23 (20th May 2016) - Ghidini, Alice; Bergquist, Helen; Murtola, Merita; Punga, Tanel; Zain, Rula; Strömberg, Roger
Abstract : Peptide nucleic acid (PNA) clamps give more stable complexes with RNA than with DNA and a BisPNA (AntimiR) invades a hairpin RNA that is a model of the microRNA miR-376b. This may be an effective way of targeting miRs. Abstract : To be able to target microRNAs also at stages where these are in a double stranded or hairpin form we have studied BisPNA designed to clamp the target and give sufficient affinity to allow for strand invasion. We show that BisPNA complexes are more stable with RNA than with DNA. In addition, 24-mer BisPNA (AntimiR) constructs form complexes with a hairpin RNA that is a model of the microRNA miR-376b, suggesting that PNA-clamping may be an effective way of targeting microRNAs.